Going places. (Economist, 2017)
The article discusses artificial intelligence with particular focus on the computer program AlphaGo developed by Google DeepMind, which plays the board game Go. Topics include the challenges of Go, the role of supervised learning in artificial intelligence, and how the AlphaGo Zero version does not rely on human input. Go matches between AlphaGo and Go champions such as Lee Sedol and Ke Jie are also discussed.